Parents' Responsibilities in Children's Education Based on Qs. At-Tahrim Verse 6 and the Hadith at Bunda Karawang Early Childhood Education Center - Fitri Kurniasari; Sumaini, Sumaini; Imas Masitoh; Tati Nurhayati Lubis (STIT Attaqwa, 2025)
This study examines parental responsibilities in early childhood education from the perspective of QS. At-Tahrim Verse 6 and the Hadith of the Prophet Muhammad (peace be upon him), and their implementation at Bunda Karawang Preschool. Parents are positioned as the primary educators responsible for fostering morals and child development from an early age. QS. At-Tahrim Verse 6 emphasizes the obligation of parents to protect themselves and their families from misguidance through proper education, while the Hadith of the Prophet Muhammad (peace be upon him) reinforces the concept of parental leadership, which carries the trust of their families. These values ​​serve as an important foundation for the implementation of early childhood education oriented towards character and spirituality formation. This study uses a qualitative approach in the form of mini-research through in-depth interviews, light observation, and documentation review. The research focused on patterns of parental involvement in children's religious education, forms of collaboration between home and school, and teacher strategies in internalizing Islamic values ​​through habituation activities at Bunda Karawang Early Childhood Education (PAUD). Data were analyzed using data reduction, data presentation, and conclusion-drawing techniques to obtain a comprehensive picture of educational practices based on the teachings of the Quran and Hadith. The results indicate that parents have a normative awareness of the importance of spiritual responsibility for their children's education, but their implementation remains varied and inconsistent within the home environment. Bunda Karawang PAUD strives to strengthen this through religious habituation, such as daily prayer, simple etiquette, and Islamic social behavior. The main challenges lie in parents' limited time, differences in religious understanding, and a lack of continuity between home and school. This research emphasizes the need for ongoing synergy between parents and PAUD institutions to ensure the effective implementation of the values ​​of QS At-Tahrim verse 6 and the Hadith in developing early childhood character. These findings contribute to strengthening the Islamic values-based family education model as the basis for care and learning in early childhood.